Calculation of multivariate normal probabilities by simulation, with applications to maximum simulated likelihood estimation - Lorenzo Cappellari; Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2006)
We discuss methods for calculating multivariate normal probabilities by simulation and two new Stata programs for this purpose: mvdraws for deriving draws from the standard uniform density using either Halton or pseudo-random sequences, and an egen function mvnp() for calculating the probabilities themselves. Several illustrations show how the programs may be used for maximum simulated likelihood estimation.
Keywords: 330